Necrosis: Cell death (Henry Stewart Talks, 2025)
Necrosis vs Apoptosis, Causes of Necrosis, Necrotic Cell Features, Inflammatory Response, Necrotic Tissue Management, Early Intervention Importance, Necrosis in Disease Management